Meningkatkan Motivasi dan Strategi Marketing Bagi Pengelola Wirausaha di Lingkungan Siswa/I SMA Global International School - Ainun Afwaniah; Aap Alhapid; Fahmi Amirudin; Alqaf Bayu Pamungkas; Acep Noval; Febby Febriana; Bela Bela (jurnal ABDIMAS Indonesia, 2025)
The Community Service Program (PKM) was implemented with the primary objective of improving the motivation and skills of Global International School high school students in managing independent business units established within the school environment. This activity was designed as a practice-based entrepreneurial development effort, especially for students directly involved in school business activities. The program was implemented through a series of training sessions covering entrepreneurial motivation, digital and conventional marketing strategies, and sales practice simulations. The motivation training aimed to build an independent and resilient mindset in facing business challenges, while the promotional strategy training emphasized the importance of branding, the use of social media, and effective communication with consumers. During the implementation process, students were encouraged to actively participate, be creative, and directly apply the material learned through simulations and group discussions. Evaluation results showed that this activity successfully increased the enthusiasm and confidence of students in running their own businesses. They also began to understand the basic concepts of branding, targeted promotional strategies, and the importance of building relationships with consumers. The enthusiasm of the participants was very high, especially during the promotional and direct sales practice. Overall, this PKM activity had a positive impact on students' mental and technical readiness to face the business world. This program also has the potential to be further developed as the basis for a practice-based entrepreneurship curriculum, as well as a medium for character building, creativity, and student independence at the secondary education level.